Evaluation of biocatalysts synthesized with lipase from Pseudomonas cepacia supported on glycol-modified MOF-199 in the synthesis of green biodiesel - Martínez Gil, José Manuel; Vivas-Reyes, Ricardo; Bastidas-Barranco, Marlón José; Giraldo, Liliana; Moreno-Piraján, Juan Carlos (Frontiers in Sustainability, 2022)
In this work, we report the synthesis and characterization of biocatalysts prepared using MOF-199 and lipase from Pseudomonas cepacia as a support, an agent for the breakdown of saturated, monounsaturated, and polyunsaturated fatty acids, the main components of palm oil (Elaeis guineensis), used to produce green biodiesel. Lipase from Pseudomonas cepacia (PCL) is used as an enzyme, which is supported by adsorption on MOF-199 (MOF-199-PCL) and another part of MOF-199 is modified with glycol as a carbon source to which PCL is supported to obtain the modified MOF (Gly@MOF-199-PCL). MOF-199 was modified by calcining a sample at 900°C for 2 h at a heating rate of 7°C/min, in an inert atmosphere and then stored in a desiccator to protect it from moisture before proceeding to adsorb PCL. Both the biocatalysts (MOF-199-PCL and Gly@MOF-199-PCL) and the supernatant liquid were characterized using Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy, energy dispersive X-ray spectroscopy (EDS or EDX), gas chromatography coupled with mass (GC-MS), and nuclear magnetic resonance (NMR). The results of the instrumental part show that both biocatalysts produce green biodiesel, which is a novel contribution to these systems.